Prevalence of allergic contact dermatitis among workers in electrotechnical industry - Łata, Alicja; Jutel, Marek (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
Introduction: A number of epidemiological studies demonstrated a relationship between allergic contact dermatitis and factories environment and work. The increase of the incidence of occupational allergic contact dermatitis among people exposed to isocyanate is observed. Aim of study: The aim of study was to evaluate the sensitization to chemical allergens, isocyanate and formaldehyde in occupational environment using patch tests. Material and methods: Patch test was performed in 194 subjects occupationally exposed to chemical factors. Most subjects tested reported intermitted or persistent appeared of skin lesions at work. Standard patch tests, 1% isocyanate diphenylmethane, 1% formaldehyde were used in all subjects. Results: Positive reaction in patch test was observed in 21 females and 10 males. Sensitization to nickel was prevalent (17 women and 2 men). Six patients showed a irritant reactions to cobalt. Several subjects showed positive reaction to terpentine oil, balsam of Peru, acid salicylic in eucerine, perfume mixture type A and para-phenylenodiamine. Among all patients three men had a positive reaction to isocyanate (MDI), no positive reaction was observed in women. None of the patients reacted to formaldehyde. Conclusions: These results show that sensitization to nickel is most prevalent in women. The most important point of this study was to indicate reaction to isocyanate. Isocyjanates present in the occupational environment of industry are the most important triggers of contact dermatitis in men. These data demonstrate that early diagnosis of isocyanate sensitivity is very important step in prevention of development of the occupational allergic contact skin diseases.